2016
DOI: 10.1016/s1470-2045(16)30095-x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic radiotherapy for the prevention of procedure-tract metastases after surgical and large-bore pleural procedures in malignant pleural mesothelioma (SMART): a multicentre, open-label, phase 3, randomised controlled trial

Abstract: SummaryBackgroundThe use of prophylactic radiotherapy to prevent procedure-tract metastases (PTMs) in malignant pleural mesothelioma remains controversial, and clinical practice varies worldwide. We aimed to compare prophylactic radiotherapy with deferred radiotherapy (given only when a PTM developed) in a suitably powered trial.MethodsWe did a multicentre, open-label, phase 3, randomised controlled trial in 22 UK hospitals of patients with histocytologically proven mesothelioma who had undergone large-bore pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 20 publications
2
94
0
3
Order By: Relevance
“…The SMART trial was a randomised, multicentre, phase III trial evaluating whether prophylactic radiotherapy reduces the incidence of procedure tract metastases after surgical and large bore pleural procedures 129 . Eligible patients were recruited from 22 UK hospitals and randomised (1:1) to immediate radiotherapy (21 Gy in three fractions over three working days), or deferred radiotherapy (same dose given if a procedure tract metastasis (PTM) developed).…”
Section: Section 12: Radiotherapymentioning
confidence: 99%
“…The SMART trial was a randomised, multicentre, phase III trial evaluating whether prophylactic radiotherapy reduces the incidence of procedure tract metastases after surgical and large bore pleural procedures 129 . Eligible patients were recruited from 22 UK hospitals and randomised (1:1) to immediate radiotherapy (21 Gy in three fractions over three working days), or deferred radiotherapy (same dose given if a procedure tract metastasis (PTM) developed).…”
Section: Section 12: Radiotherapymentioning
confidence: 99%
“…A recommendation from this study is to strongly consider port side radiation post procedure in patients with mesothelioma to decrease the risk of tract tumor seeding with malignant cells (48). Recent studies have shown no benefit of routine use of prophylactic radiotherapy following pleural interventions in patients with malignant mesothelioma (49,50). Figure 6 shows a modified diagnostic algorithm for patients with suspected MPE.…”
Section: Mt and Video-assisted Thoracoscopic Surgery (Vats)mentioning
confidence: 99%
“…Prior studies have reported that pain related to procedure-tract metastasis is generally mild to moderate in intensity and is responsive to treatment [21, 42, 45]. Although the incidence of CTM was higher than previously reported, we would not recommend avoidance of IPCs due to the clear symptomatic benefit.…”
Section: Discussionmentioning
confidence: 72%
“…The 2016 SMART trial by Clive et al [42], which included 25 patients (12%) with IPCs, compared immediate (prophylactic) radiotherapy to deferred radiotherapy (following diagnosis of tract metastasis). There was no difference in quality of life, chest pain, analgesia requirement, or overall development of procedure tract metastasis between groups.…”
Section: Discussionmentioning
confidence: 99%